Optimizing the use of partographs by midwives in early detection of labor complications: analysis of influencing factors - Yuliastuti, Erni; Fathurrahman, Fathurrahman; Rafidah, Rafidah; Syahrianti, Syahrianti; Sarita, Sultina; Rosana, Dina (Media Penelitian dan Pengembangan Kesehatan, 2026)
Background: The use of partographs in obstetric care is an important topic, especially in low- and middle-income countries, including Indonesia, which face high maternal and neonatal mortality rates. Objective: This study aimed to explore and analyze factors influencing midwives' use of the partograph for early detection of labor complications. Methods: This study employed a non-experimental quantitative approach with a cross-sectional design to analyze factors influencing partograph use by midwives. The study population was 135 midwives in Hulu Sungai Utara Regency, with a sample of 101 midwives determined using a simple random sampling technique. The dependent variable was partograph utilization, while the independent variables included midwives' knowledge, attitudes, motivation, perception of supervision, training, length of service, age, and education level. Data were collected through a structured questionnaire and observation sheet. Data analysis used the chi-square test and multiple logistic regression to identify relationships between variables influencing partograph utilization. Results: The education was significantly associated with partograph utilization (p=0.001; OR 6.0), with midwives with higher education being more likely to use it. Conversely, length of service ≥5 years was associated with decreased partograph utilization (p=0.000; OR 0.05). In addition, motivation (p=0.002; OR 1.6) and supervision (p=0.032; OR 1.7) also positively influenced partograph use. The logistic regression model showed that higher education increased the probability of partograph use (Exp(B)=11.172), while longer work experience decreased the probability (Exp(B)=0.028). Conclusion: Higher education significantly increased partograph use, while work experience above 5 years decreased its use. Motivation and supervision also positively contributed to optimal partograph use.